1970
DOI: 10.1111/j.1939-0025.1970.tb00721.x
|View full text |Cite
|
Sign up to set email alerts
|

School adjustment and behavior of children hospitalized for schizophrenia as adults.

Abstract: Childhood public school records of 30 nonmigratory, hospitalized schizophrenic adults were compared with those of 90 matched control children presumed to have become normal adults. It was concluded that a substantial proportion of children destined to be schizophrenic as adults can be identified by their behavior in public school before they break down.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
3

Year Published

1979
1979
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 30 publications
3
27
0
3
Order By: Relevance
“…More than half of the probands committed violent crimes before their first admission, suggesting that factors affecting violent behavior are present prior to the onset of psychosis. Thus, these data add to a large body of knowledge on pre-morbid behavior abnormalities in patients with schizophrenia (Watt et al 1970;Done et al 1994;Jones, 1997;Bearden et al 2000;Reichenberg et al 2002).…”
Section: Discussionmentioning
confidence: 81%
“…More than half of the probands committed violent crimes before their first admission, suggesting that factors affecting violent behavior are present prior to the onset of psychosis. Thus, these data add to a large body of knowledge on pre-morbid behavior abnormalities in patients with schizophrenia (Watt et al 1970;Done et al 1994;Jones, 1997;Bearden et al 2000;Reichenberg et al 2002).…”
Section: Discussionmentioning
confidence: 81%
“…People who were admitted to hospital with schizophrenia had lower intelligence quotients (IQ) than their siblings and classmates1,2 and were also reported by their teachers as exhibiting deviant behaviour 3,4. These abnormalities (apparently confined to the boys) have been attributed to neurodevelopmental impairment, susceptibility to psychosocial stressors, or an interaction of these two possible factors 5…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that socially incompetent children are more likely to drop out of school (Ullmann, 1957), become juvenile delinquents (Roff, Sells, and Golden, 1972), underachieve academically, and exhibit high levels of physical and verbal aggression (McCandless, 1967). Similarly, several retrospective studies of adult psychiatric patients (e.g., Pritchard and Graham, 1966;Watt, Stolurow, Lubinsky, and McClelland, 1967) have indicated that those patients diagnosed as schizophrenic, sociopathic, and/or mentally deficient frequently have psychiatric records dating from early childhood.…”
mentioning
confidence: 99%